Variation in growth, flowering and seed yield of satin flower (Godetia grandiflora) planted on different dates - SHARMA, PRIYANKA; GUPTA, Y C; DHIMAN, S R; SHARMA, PUJA; BHARGAVA, BHAVYA (The Indian Journal of Agricultural Sciences, 2016)
The effect of climatic conditions and planting dates on growth, flowering and seed production of satin flower (Godetia grandiflora Lindl.) under mid hill conditions of Himachal Pradesh during 2010-11 and 2011-12 were investigated. Plantings were done at an interval of 15 days starting from 17 September in both the years with planting dates as; 17 September, 2 October, 17 October, 1 November, 16 November and 1 December under randomized block design. The maximum plant height (68.35 cm), plant spread (50.66 cm), stem length (58.38 cm), duration of flowering (33.91 days), number of flowers/stem (central and side; 110.08 and 15.74), number of capsules/plant (327.50), number of seeds/capsule (90.69) and seed yield/plant (9.18 g) were recorded when planting was done on 17 September. However, earliest visible flower bud formation (121.36 days), days to flowering (151.53) and capsule formation (205.42 days) were observed in 1 December planting.